A Pilot Study Applying Social Cognitive Theory to Predict HPV Vaccination Intentions of Unvaccinated College Women. Issue 4 (1st October 2016) - Catalano, Hannah Priest; Knowlden, Adam P.; Sharma, Manoj; Franzidis, Alexia
ABSTRACT: Although college-aged women are at high risk for human papillomavirus (HPV) infection, many college women remain unvaccinated against HPV. Testing health behavior theory can assist sexuality educators in identifying behavioral antecedents to promote behavior change within an intervention. The purpose of this pilot study was to utilize social cognitive theory (SCT) to predict unvaccinated college women's intentions to receive the HPV vaccine within the next six months. A total of 197 unvaccinated college women ages 18–26 attending a large public southeastern university in the United States completed an online questionnaire to assess SCT constructs. Expectations, HPV knowledge, self-efficacy to get the HPV vaccine, situational perception, self-control to get the HPV vaccine, and self-efficacy in overcoming barriers to get the HPV vaccine were regressed on HPV vaccination intentions using the stepwise method. Self-control ( p < 0.001, β = .292) and situational perception ( p < 0.001, β = .332) were significant predictors of intentions to receive the HPV vaccine, explaining 23.5% of its variance. The results of this pilot study suggest that sexuality educators should aim to increase self-control and situational perception in order to increase HPV vaccination intentions among college women.